The Professional Profile of the Architect - Romoleroux, Julio (Revista Universidad de Guayaquil, 2009)
A professional profile is not so much what one can do according to their "field" based on their academic training, but rather the qualities or attributes that allow them to act professionally according to that training.The profile of any higher education professional should be permanently linked to social interests and demands, in order to contribute with their knowledge to individual and collective development and well-being.